Assistance for Child-Friendly Schools for Elementary School Teachers in Pekalongan Regency Through the Workshop on PSGA UIN K.H Abdurrahman Wahid - Ningsih Fadhilah; Ana Chonitsa; Amma Chorida Adila (Pengabdian: Jurnal Abdimas, 2024)
Background. Child-friendly schools are a government program that is still being intensively carried out at schools and madrasas in Indonesia. Purpose. The aim of the research is to provide assistance to Child Friendly Schools in solving problems related to the implementation of Child Friendly Schools in the Madrasah environment Method. This child-friendly school mentoring method consists of four stages of activity, namely activity preparation, implementation, and activity closing. This activity lasted for two days on 5-6 June 2023 at the integrated Lecture Building of UIN K.H Abdurrahman Wahid Pekalongan. Researchers in conducting research data analysis by drawing conclusions on the mentoring activities that have been carried out. Results. Child-friendly school assistance is a community service carried out by the Center for Gender and Child Studies at UIN K.H Abdurrahman Wahid Pekalongan in planning a child-friendly school program for Madrasah Ibtidaiyah in Pekalongan Regency. Meanwhile, this activity is useful in holding group discussion forums to deal with problems faced by today's children, providing protection and prevention against hazards that at times threaten the safety of school students. The three stages of implementing child-friendly schools in Madrasah Ibtidaiyah are planning, preparation and collaboration Conclusion. Assistance and implementation of child-friendly schools can be effective as long as all elements, both schools, communities and universities are mutually irrational to create child-friendly schools.